A greener gas grid: What are the options. (July 2018) - Speirs, Jamie; Balcombe, Paul; Johnson, Erin; Martin, Jeanne; Brandon, Nigel; Hawkes, Adam
Abstract: There is an ongoing debate over future decarbonisation of gas networks using biomethane, and increasingly hydrogen, in gas network infrastructure. Some emerging research presents gas network decarbonisation options as a tractable alternative to 'all-electric' scenarios that use electric appliances to deliver the traditional gas services such as heating and cooking. However, there is some uncertainty as to the technical feasibility, cost and carbon emissions of gas network decarbonisation options. In response to this debate the Sustainable Gas Institute at Imperial College London has conducted a rigorous systematic review of the evidence surrounding gas network decarbonisation options. The study focuses on the technologies used to generate biomethane and hydrogen, and examines the technical potentials, economic costs and emissions associated with the full supply chains involved. The following summarises the main findings of this research. The report concludes that there are a number of options that could significantly decarbonise the gas network, and doing so would provide energy system flexibility utilising existing assets. However, these options will be more expensive than the existing gas system, and the GHG intensity of these options may vary significantly. In addition, more research is required, particularly in relation to the capabilities of existing pipework to transport hydrogen safely. Highlights: Summarises a study into the future decarbonisation options for low pressure gas networks. Presents routes to biomethane and hydrogen production, including network impacts. Presents estimates of cost and greenhouse gas emissions for these routes to low carbon gas.